Evaluation of Batch Culture Phytoremediation Process using Local Hydromacrophytes to Reduce Synthetic Pesticide Residue in Contaminated Irrigation Water - Catur Retnaningdyah; Endang Arisoesilaningsih (Institute for Research and Community Services (LPPM) ITB, 2019)
The aim of this study was to evaluate the effectivity of batch culture phytoremediation to remediate irrigation water that was contaminated with 6.4 µL/L synthetic pesticide Prevathon. This was a true experimental research study using a completely randomized design, conducted in a 30 L bucket with sand and gravel as the substrate. The treatment comprised five types of hydromacrophytes (emergent, floating leaf, submerged, polyculture and control without plants), repeated three times at the same time. The effectiveness of the phytoremediation model was determined by water physicochemical parameters, periphyton diversity, percentage of pollution tolerant values (%PTV) and trophic diatom index (TDI) on day 6, 13, 29 and 37 after incubation. The research results showed significantly decreased values of biochemical oxygen demand, turbidity, bicarbonate, nitrate, orthophosphate, total phosphate and free chlorine after incubation for 6 days; decreased concentration of chemical oxygen demand after incubation for 13 days. The water quality improved from slightly and moderately polluted (diversity index 1.6-2.8) to clean and slightly polluted (diversity index 2.8-4.2), from moderately and heavily organically polluted (PTV 40.0-93.7%) to slightly organically polluted and free of organic pollution (PTV 2.4-34.1%), and from meso-eutrophic and eutrophic (TDI 37.4-70.4) to oligo and meso-eutrophic (TDI 13.7-26.4).